Qualidade Pós-Colheita da Cebola Roxa Produzida no Sertão Paraibano - Albuquerque, Jose Ricardo Tavares de; Costa, Franciscleudo Bezerra da; Pereira, Emmanuel Moreira; Rocha, Thayse Cavalcante da; Lins, Hamurábi Anízio (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2013)